Kolej Komuniti Arau Perlis (KKAP) Network Modeling Using OMNeT++ - Mohd Aishamuddin, Yaakob (2012)
Computer networks have become extremely important in our present-day society. A majority of companies depend on the proper functioning of their networks for communications, administration, automation, e-business solutions and other corporate functions. Outage of the network can cost a company millions of money. To avoid these problems, system managers need professional tools to help them with the design and maintenance of computer networks. A simulation tool offers a way to predict the impact on the network of a hardware upgrade, a change in topology, an increase in traffic load or the use of a new application.OMNeT++ offers a number of tools specifically designed for these purposes. The objective of this project is to design and simulate existing network in Kolej Komuniti Arau Perlis (KKAP) building using OMNeT++ simulation environment. KKAP may deploy internal mesh network that provide better communication inside the campus. inter-department and levels of the actual KKAP's buildings. From the simulation, data are collected as if a real system were being observed. The results are expected to show that OMNeT++ provides credible simulation results close to a real system. Thus, in future these models are expected to assist KKAP to explore new design options without disrupting the existing systems.